Efficacy of pump-controlled selective antegrade cerebral perfusion in total arch replacement: A propensity-matched analysis - Liu, Yu; Jiang, Hui; Wang, Bin; Yang, Zhonglu; Xia, Lin; Wang, Huishan (Frontiers in Surgery, 2022)
Background: Pump controlled selective antegrade cerebral perfusion (PC-SACP) in total arch replacement (TAR) can regulate cerebral flow exactly, which might be benefit for cerebral protection. However, the safety of PC-SACP for TAR combined with frozen elephant trunk implantation (FET) in patients with acute Type A dissections (ATAAD) is ambiguous. Methods: A total of 192 patients with ATAAD underwent TAR at our institution from October 2019 to July 2021. Patients were divided into 2 groups based on PC-SACP used: PC group (SACP carried out by separate pump, n=35), Control group (SACP carried out as traditional method, n=157). Patients under PC-SACP were propensity score matched to patients without PC-SACP resulting in 35 pairs of patients. Results: Preoperative characteristics were similar between the two groups, including age, gender, weight, preoperative creatinine and so on. CPB time, cross-clamp time, CA time and minimum nasopharyngeal temperature between the two groups have no significant difference. However, the SACP time (54 vs 39, P=0.000) in PC group was significant longer than in control group. The incidence of TND (5.7% vs 11.4, P=0.393) have a lower trend in PC group compared with control group. However, the difference has no significance. Other clinical outcomes have no significant differernce. Conclusions: Pump controlled selective antegrade cerebral perfusion in total arch replacement was safe and feasible, which might be benefit for avoiding neuroinjury caused by “luxury” perfusion.